S1P defects cause a new entity of cataract, alopecia, oral mucosal disorder, and psoriasis‐like syndrome - Fuying Chen; Cheng Ni; Xiaoxiao Wang; Ruhong Cheng; Chaolan Pan; Yumeng Wang; Jianying Liang; Jia Zhang; Jinke Cheng; Y Eugene Chin; Yi Zhou; Zhen Wang; et al. (EMBO Molecular Medicine)
Abstract In this report, we discovered a new entity named cataract, alopecia, oral mucosal disorder, and psoriasis‐like (CAOP) syndrome in two unrelated and ethnically diverse patients. Furthermore, patient 1 failed to respond to regular treatment. We found that CAOP syndrome was caused by an autosomal recessive defect in the mitochondrial membrane‐bound transcription factor peptidase/site‐1 protease (MBTPS1, S1P). Mitochondrial abnormalities were observed in patient 1 with CAOP syndrome. Furthermore, we found that S1P is a novel mitochondrial protein that forms a trimeric complex with ETFA/ETFB. S1P enhances ETFA/ETFB flavination and maintains its stability. Patient S1P variants destabilize ETFA/ETFB, impair mitochondrial respiration, decrease fatty acid β‐oxidation activity, and shift mitochondrial oxidative phosphorylation (OXPHOS) to glycolysis. Mitochondrial dysfunction and inflammatory lesions in patient 1 were significantly ameliorated by riboflavin supplementation, which restored the stability of ETFA/ETFB. Our study discovered that mutations in MBTPS1 resulted in a new entity of CAOP syndrome and elucidated the mechanism of the mutations in the new disease.